Comparative study on pump wavelength dependent efficiency in Nd:YVO4 - Schneewind Merle; Spiekermann Stefan; Weßels Peter; Neumann Jörg; Kracht Dietmar (EPJ Web of Conferences, 2022)
The influence of the pump wavelength on the heat load and efficiency of Nd:YVO4 crystals is investigated with a specially designed crystal mount. The measurements indicate that the change in heat load in the crystal can be solely ascribed to the difference of quantum defects and no further non-radiative effects.